Electrical characterization of organic based transistors: stability issues - Gomes, Henrique L. (2015)
An investigation into the stability of metal insulator semiconductor (MIS) transistors based on alpha-sexithiophene is reported. In particular the kinetics of the threshold voltage shift upon application of a gate bias has been determined. The kinetics follow a stretched-hyperbola type behavior, in agreement with the formalism developed to explain metastability in amorphous-silicon thin film transistors. Using this model, quantification of device stability is possible. Temperature-dependent measurements show that there are two processes involved in the threshold voltage shift, one occurring at T approximate to 220 K and the other at T approximate to 300 K. The latter process is found to be sample dependent. This suggests a relation between device stability and alpha-sexithiophene deposition parameters. Copyright (c) 2005 John Wiley A Sons, Ltd.